2015
DOI: 10.1016/j.schres.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive insight, treatment utilization, and cognitive training outcomes in schizophrenia

Abstract: Background The degree to which people with schizophrenia show awareness of cognitive dysfunction and whether this neurocognitive insight affects treatment use or outcome is understudied. We aimed to examine neurocognitive insight among a treatment-seeking sample of patients with psychotic disorders, and whether neurocognitive insight affected treatment utilization or outcome. Method 69 individuals with schizophrenia-spectrum disorders enrolled in a trial comparing Compensatory Cognitive Training (CCT) to sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 16 publications
2
20
2
Order By: Relevance
“…Several findings emerged from this meta-analysis and can be summarized as follows: 1) individuals with schizophrenia reported higher cognitive complaints than nonclinical controls; 2) modest associations between measures of objective and subjective cognition were found (the higher for problem-solving domain) 3) these relationships were higher when the study used the SSTICS to measure self-reported cognitive functioning in comparison with other scales, and 4) a weak association was found between depressive symptoms and cognitive complaint. Interestingly, several studies have been published after this meta-analysis, reporting as a whole similar results (19)(20)(21)(22). However, and surprisingly, none of these studies about metacognitive awareness of cognitive functioning in schizophrenia examined and compared correlations between measures of objective and subjective cognition in a comparison group of non-clinical controls.…”
Section: Introductionmentioning
confidence: 80%
“…Several findings emerged from this meta-analysis and can be summarized as follows: 1) individuals with schizophrenia reported higher cognitive complaints than nonclinical controls; 2) modest associations between measures of objective and subjective cognition were found (the higher for problem-solving domain) 3) these relationships were higher when the study used the SSTICS to measure self-reported cognitive functioning in comparison with other scales, and 4) a weak association was found between depressive symptoms and cognitive complaint. Interestingly, several studies have been published after this meta-analysis, reporting as a whole similar results (19)(20)(21)(22). However, and surprisingly, none of these studies about metacognitive awareness of cognitive functioning in schizophrenia examined and compared correlations between measures of objective and subjective cognition in a comparison group of non-clinical controls.…”
Section: Introductionmentioning
confidence: 80%
“…In addition, some neuropsychiatric or neurodegenerative diseases such as depression (Zaninotto et al, 2015 ), schizophrenia (Burton and Twamley, 2015 ), and AD (Takeda et al, 2014 ) are associated with memory loss. In this regard, CREB has been postulated to change the sensitivity of the nucleus accumbens to rewarding and aversive drugs (Bilbao et al, 2014a , b ).…”
Section: Creb and Memorymentioning
confidence: 99%
“…Those who are better aware of their deficits are not associated with a lower use of treatment, nor with a lesser deterioration of executive function. But they do have better results in the rehabilitation of some cognitive domains, in adherence to treatment and in their functional capacity [41,42].…”
Section: Cognitive Deficit In Schizophreniamentioning
confidence: 99%